Against the Grammarians by Sextus Empiricus: annotated translation, part three (M 1. 169-247) - Prezotto, Joseane Mara (Revista Archai, 2018)
Annotated partial translation (M 1. 169-247) of the treatise Against the Grammarians written by the Pyrrhonian skeptical philosopher Sextus Empiricus (II C.E.). In this section, the philosopher continues his attack against the technical part of grammar, addressing the grammatical treatment of orthography, Hellenism and etymology and advocating, against the technical criterion of the grammarians, the practical criterion of common use. The space he assigns to arguments that are most likely to be of epicurean origin rather than skeptical is considerable. This might suggest that its main source was a work of attack on grammatical doctrine, along the lines of the epicurean tradition of polemic against disciplines that would claim to be at the forefront of philosophy. The notes of the translation seek to clarify questions underlying the Sextian argument, to justify our translational choices, and to provide information that makes it possible to draw parallels between the passage in question and other works by the author or the period.